THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR IMPROVING INTERDISCIPLINARY INTEGRATION IN PHYSICS EDUCATION - Ergasheva Maxfuza Saliyevna (Modern American Journals, 2025)
In the context of rapid scientific, technological, and socio-economic development of the twenty-first century, the transformation of educational paradigms has become an inevitable requirement for ensuring the quality and sustainability of learning outcomes. In this regard, interdisciplinary integration is increasingly recognized as a key methodological strategy that enables the formation of holistic scientific thinking, the development of higher-order cognitive skills, and the meaningful transfer of knowledge across disciplinary boundaries. Physics education, due to its fundamental nature and close conceptual connections with mathematics, chemistry, biology, and information technologies, occupies a central position in the implementation of interdisciplinary approaches. This study examines the theoretical and methodological foundations of improving interdisciplinary integration in physics education, with a particular focus on academic lyceums as institutions providing advanced and pre-professional training. The research analyzes contemporary pedagogical theories, methodological models, and experimental practices aimed at enhancing interdisciplinary coherence in physics instruction. The findings demonstrate that interdisciplinary-integrated physics teaching significantly improves students’ conceptual understanding, problem-solving abilities, and learning motivation, thereby contributing to the development of scientifically literate and professionally oriented graduates.
Keywords: Physics education, interdisciplinary integration, academic lyceum, competency-based approach, STEAM education, educational methodology, didactics.